The role of social values in preventing crime A field study on a sample of students of the Faculties of the University of Sebha (Journal of Human Sciences, 2018)
The importance of studying social values ??and their role in preventing crime within communities are important topics that have received a lot of attention by researchers and those interested in examining humanities. The research dealt with the role of values ??in the prevention of crime among students of the faculties of medicine and arts at the University of Sabha. It is an applied descriptive and analytical study done through a sample, in order to identify the values ??that work to prevent crime. This is done by knowing the differences between the elements of the values ??defined in the research among the students of the two faculties. The results of this study contribute to the definition of values ??and their role in the prevention of crime in its five dimensions: the value of loyalty to the home country, the value of trust, the value of respect for the neighbor, the value of respect for public property, and the value of love of work. These values ??can be viewed as restrictions and controls regulating tendencies Selfish or aggressive impulses, as well as work to strengthen social cohesion. Values ??play a role in controlling behavior and prompt the individual to be consistent with the behavior of others. It reduces crime and delinquency in society, and contributes to inculcating active values ??in young people.